Analisis Model Simpal Kausal: Peranan Variabel Amanah dalam Kegiatan Pengadaan Barang dan Jasa Pemerintah - Hendrawangsa, Permana; Permana, Prama (Jurusan Ekonomi Pembangunan, Fakultas Ekonomi, Universitas Siliwangi, 2020)
Humans have the title of khalifah fi al-ardh with which humans are assigned to manage life to achieve prosperity both in the world and the hereafter. Carrying out the mandate is an arduous task because it demands self-determination. The application of the mandate should include all aspects of life. This study aims to analyze the role of the trust (amanah) variable in the activities of government procurement of goods and services which in turn will have an impact on economic development. The results of this study reveal the key success factors that are the leverage for government procurement of goods and services including the provision of educational facilities and infrastructure. By using the Causal Loop Model analysis, it was found that there is a very important role between the application of the trust variable to the success of educational infrastructure development activities. The object of this research is the education facilities and infrastructure procurement activities carried out in Siliwangi University. This quantitative research uses the concept of all-round system thinking with mixed methods and the Causal Loop Model according to Maani and Cavana. Through these mixed concepts, the key success factors in the form of factors with high leverage are obtained. After causal loop modeling, it was found that the Amanah variable has as many as 16 loops with a tree of 9 variables; E-Tender variable has 16 loops with 8 variables using tree; The Value for money variable has 16 loops with 5 tree uses variables. Thus, the leverage variable is obtained is